The Effect 0f Warm-up on Tethered Front Crawl Swimming Forces - Neiva, Henrique (2011)
This study was conducted to determine the effect of warm-up on high-intensity front crawl tethered swimming and thus to better understand possible variations in the force exerted by the swimmers. Ten male national level swimmers (mean ± SD; age 15.3 ± 0.95 years old, height: 1.73 ± 5.2 m, body mass: 64.3 ± 7.8 kg, Fat mass 8.31 ± 3.1 kg) participated in this study. After a typical competition warm-up, the subjects performed a 30 s tethered swimming all-out effort in front crawl swimming technique. The same test was repeated in the day after but performed without warming up. Capillary blood lactate concentration was assessed before and after the swimming test and the Borg ratings of perceived exertion scale was used. Without a previous warm-up, the mean ± SD values of maximum and mean forces were 299.62 ± 77.56 N and 91.65 ± 14.70 N, respectively. These values were different (p<0.05) from the values obtained with warm-up (351.33 ± 81.85 N and 103.97 ± 19.11 N). Differences were also observed when regarding to the forces relative to body mass. However, the values of lactate net concentrations after the test performed with and without warm-up were not different (6.27 ± 2.36 mmol·l(-1) and 6.18 ± 2.353 mmol·l (-1)) and the same occurs with the values of ratings of perceived exertion (15.90 ± 2.42 and 15.60 ± 2.27). These results suggest an improvement of the maximum and mean force of the swimmer on the tethered swimming due to previous warm-up.